Em busca dos fatores críticos de sucesso para implantação de uma gestão intra-empreendedora - Machado, Ricardo Jose da Silva (2005)
This research propounds to investigate if the critics factors of success that we can find in intrapreneuring the theory about intrapreneuring are the sarne in organizations that they use the intra-enterprising rnanagernent. For this, we realized two researches of theoretical review. The first one, we study authors where they consider entrepreneurship and intrapreneuring to identify critics factors of success to put in practice the intrapreneuring. The second one, using specifics authors of each subject about cntics factors of success, how they see this managernent organization process. Afier, we researched organizations where they are applying the corporative entrepreneurship process in their management to identify what would be the critics factors of success to put in practice the intrapreneuring managernent. Iii this research, we mcd to identify what would be the paths that the organizations used to put in practice the intrapreneuring rnanagernent. To collect the data base, we applied one organized formulary like principal toil to get the field information. The results were dernonstrated in this research through by tables, graphics and figures. These results show the application of critics factors ofsuccess more important to get a superior participation ofwork people through ofthe intrapreneuring management. They show either what the factors positives and limitations for your application.